Electromyographical, ultrasonographical and morphological modifications in semitendinous muscle after transposition as ventral perineal muscle flap - Mortari, A. C.; Rahal, Sheila Canevese [UNESP]; Resende, LAL; Dal-pai-silva, M.; Mamprim, Maria Jaqueline [UNESP]; Correa, M. A.; Antunes, SHS (Blackwell Publishing, 2005)
The aim of this study was to evaluate modifications occurring in semitendinous muscle after transposition as a ventral perineal muscle flap using electromyography, ultrasonography, and morphological studies. Ten male crossbreed dogs of 3-4 year old were used. The left semitendinous muscle was cut close to the popliteus lymph node, rotated and sutured at the perineal region. The contralateral muscle was considered as control. Motor nerve conduction studies of both sciatic-tibial nerves, and electromyographic and ultrasonographic examinations of both semitendinous muscles were performed before surgery and 15, 30, 60, and 90 days postoperatively. Semitendinous muscle samples were collected for morphological analysis 90 days after surgery. No alterations were observed in clinical gait examinations, or in goniometrical and electroneuromyographical studies in pelvic limbs after surgery. Electromyography demonstrated that the transposed muscle was able to contract, but atrophy was detected by ultrasonography and morphological analysis.